2008
DOI: 10.1186/1757-1626-1-142
|View full text |Cite
|
Sign up to set email alerts
|

Granular cell tumour of the pectoral muscle mimicking breast cancer

Abstract: We describe the case of a 55 year old female who presented with a mass in her right breast. Mammography confirmed a 2 × 2 cm lump, suspicious of malignancy. The lesion was widely resected. Histological examination revealed this to be a benign granular cell tumour.Granular cell tumour is a rare tumour that very occasionally presents within the breast. It is possibly of Schwann cell origin. Clinical features and subsequent investigations may be suggestive of breast malignancy. Tumour cells showing positive immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 7 publications
4
31
0
2
Order By: Relevance
“…Aoyama et al (3), reported in their study of six cases of GCTs, a 54-year-old woman with a GCT in the left axillary cavity, which is very similar to our patient. Another patient with similar location of GCT in the upper outer quadrant of the right breast which appeared to be attached to the underlying pectoralis major muscle, was described by Patel et al (9). The mammographic appearence of the GCT was very similar to the patient from our case report.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Aoyama et al (3), reported in their study of six cases of GCTs, a 54-year-old woman with a GCT in the left axillary cavity, which is very similar to our patient. Another patient with similar location of GCT in the upper outer quadrant of the right breast which appeared to be attached to the underlying pectoralis major muscle, was described by Patel et al (9). The mammographic appearence of the GCT was very similar to the patient from our case report.…”
Section: Discussionsupporting
confidence: 85%
“…Microcalcifications are not normally a feature of GCTs. On ultrasound, GCTs can present as solid, poorly marginated lesions with marked posterior shadowing or as more benign-appearing well-circumscribed solid masses (8,9). MRI findings in a patient with GCT were described by Scaranelo et al (10).…”
Section: Discussionmentioning
confidence: 95%
“…Lymph node excision or sentinel lymph node biopsy is not indicated except malignant cases or colocalisation with malignancy. Although conservative approach has been suggested (Patel et al, 2008) it is not accepted. Extensive and/or combined treatment as for breast cancer should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…GCT of the breast arises from intralobular breast stroma and occurs within the distribution of the cutaneous branches of the supraclavicular nerve [7,8]. It usually presents as a solitary non tender nodule but not uncommonly is multifocal and a manifestation of multicentric disease [7].The tumor is often found in the upper inner quadrant unlike breast cancer that is found in the upper outer quadrant [8,9].…”
Section: Review Of Literaturementioning
confidence: 99%
“…It usually presents as a solitary non tender nodule but not uncommonly is multifocal and a manifestation of multicentric disease [7].The tumor is often found in the upper inner quadrant unlike breast cancer that is found in the upper outer quadrant [8,9]. Since the tumor affects the innervation of the skin, contractions or shrinkage of the skin sometimes occur.…”
Section: Review Of Literaturementioning
confidence: 99%